2015
DOI: 10.3390/s150306996
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Prediction Model Based on a Neural Network with Dynamic Windows

Abstract: Tracking degradation of mechanical components is very critical for effective maintenance decision making. Remaining useful life (RUL) estimation is a widely used form of degradation prediction. RUL prediction methods when enough run-to-failure condition monitoring data can be used have been fully researched, but for some high reliability components, it is very difficult to collect run-to-failure condition monitoring data, i.e., from normal to failure. Only a certain number of condition indicators in certain pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Based on the learned state transition function and real-time information of the fault indicator, the PF algorithm was used for RUL prediction of the gear subjected to wear mode of failure. Similar study is reported by Zhang et al 7 who proposed an artificial neural network (ANN) model for predicting the trend of the sideband based HI.…”
Section: Introductionsupporting
confidence: 82%
“…Based on the learned state transition function and real-time information of the fault indicator, the PF algorithm was used for RUL prediction of the gear subjected to wear mode of failure. Similar study is reported by Zhang et al 7 who proposed an artificial neural network (ANN) model for predicting the trend of the sideband based HI.…”
Section: Introductionsupporting
confidence: 82%
“…There are mainly artificial intelligence methods and statistical data-driven methods. Among them, artificial intelligence methods include support vector machine regression [9], correlation vector machine [10], neural network [11,12], ant colony algorithm [13], etc. This type of method is based on a large amount of degradation data.…”
Section: Introductionmentioning
confidence: 99%
“…During design, each train-track component is associated with one or more physics comprehension which favors the stability of forecasting the growing deterioration rate using model oriented methods even though in most cases majority of component attitudes are nonlinear. To counter the nonlinearity issues, many authors have valoralised the use of AI ideas center on neural network, fuzzy logic, Markov Models, particle filtering and other genetic algorithms [3] [4]. Excessive usage of time during execution and as such lack of human comprehension due to their hidden attitude are their negative motivation when relying on them.…”
Section: Introductionmentioning
confidence: 99%